Educational Quality and Reliability of YouTube Content Related to Musculoskeletal Ultrasound - Akkaya, Selcuk; Saglam Akkaya, Gonca (Archives of Rheumatology, 2025)
Background/Aims: YouTube’s growing popularity as an educational resource for musculoskeletal ultrasound (MSKUS) raises questions about its potential to supplement medical education. This study evaluates MSKUS-related YouTube content comprehensively to determine its potential as a supplementary tool in medical education. Materials and Methods: A cross-sectional analysis was performed on 151 YouTube videos related to MSKUS. Video characteristics and viewer interaction metrics were recorded. Video popularity was quantified using the Video Power Index. The Global Quality Score (GQS), the Quality Criteria for Consumer Health Information (DISCERN), and the Medical Quality Video Evaluation Tool (MQ-VET) were employed to assess the educational value and quality of the videos. Video reliability was evaluated using the Journal of the American Medical Association (JAMA) Benchmark Criteria. Results: The most frequent MSKUS topic covered was shoulder ultrasound (29.8%), primarily focusing on anatomical landmarks (38.7%). Educational quality assessment indicated that 40.4% of videos were classified as low quality by the GQS. DISCERN rated 43.7% of videos as “very poor” quality, whereas MQ-VET scored 25.8% as average quality. The JAMA criteria indicated that 69.5% of the videos provided only partially sufficient information. No videos cited clinical guidelines, 24.5% provided references, and 18.5% included captions. Academic sources demonstrated significantly higher quality (DISCERN: P = .018; JAMA: P = .015; MQ-VET: P = .009). Videos with captions and references/citations demonstrated significantly higher GQS, DISCERN, JAMA, and MQ-VET scores (all P < .001). Diagnostic videos had higher GQS (median 3 vs. 2; P = .021) and JAMA scores (median 2.5 vs. 2; P = .032) compared to injection videos. Conclusion: This study highlights the inconsistent quality of YouTubebased MSKUS educational content. While academic and well-referenced videos are of high quality, unvetted content often lacks accuracy, making uncurated YouTube videos unreliable for clinical learning. It is recommended that educators guide learners toward content from academic institutions or highly engaged videos with cited guidelines/sources. Standardized guidelines are crucial for integrating trustworthy YouTube MSKUS content into medical curricula.